A dual readout embryonic zebrafish xenograft model of rhabdomyosarcoma to assess clinically relevant multi-receptor tyrosine kinase inhibitors - Wragg, Joseph W.; Gray, Emma L.; Monteiro, Rui; Morris, Jo R.; Beggs, Andrew D.; Müller, Ferenc; Gatz, Susanne A. (Frontiers in Oncology, 2025)
BackgroundRhabdomyosarcoma (RMS) is a highly aggressive soft tissue sarcoma, affecting children and adolescents, with poor prognosis in some patient groups. Better therapeutic regimens and preclinical models to test them in are needed. Multi-receptor tyrosine kinase inhibitors (MRTKIs) are licensed for adult indications and explored in the clinic in sarcoma patients. The MRTKI Regorafenib is currently assessed in the relapse setting in patients with RMS (NCT04625907). Reliable biomarkers of response for MRTKIs are lacking. MRTKIs act not only against the cancer cell, but also the supporting stroma, particularly the vasculature. The embryonic zebrafish is translucent and allows assessment of this interaction with high-throughput in vivo imaging.MethodsA new preclinical embryo zebrafish xenograft model was developed using Tg(flk1:GFP) (blood vessel reporter) transgenic zebrafish embryos inoculated in the yolk with fluorescently labelled cells from 7 different RMS cell lines (fusion-positive (FP): Rh4, Rh30, Rh41, RMS-01, fusion-negative (FN): RD, JR1, SMS-CTR), and patient-derived cells IC-pPDX-104 at 50 hours post-fertilization and incubated at 34°C for up to 70 hours. Xenografts and vessel beds were imaged and analysed using custom FIJI pipelines. MRTKIs regorafenib and infigratinib were used at a concentration of 0.1uM added to the fish water 4 hours post cell inoculation. Pro-angiogenic growth factors VEFG-A, FGF-2 and PDGF-BB were measured in conditioned media of each cell line.ResultsAll 7 RMS cell lines and the patient-derived cells engrafted with tumour burden assessment by fluorescent imaging and direct cell counting indicating adequate growth and high cell viability during the observation period. RMS tumours induced neo-vascularisation towards the tumour and increased density of proximal vessel beds. MRTKI treatment revealed a greater tumour-intrinsic sensitivity of FP cells, but identified a significant blockade of neo-vascularisation across all RMS lines, with regorafenib response correlated with secretion of VEGF-A.ConclusionWe have developed an embryonic zebrafish xenograft model of RMS, which allows assessment of tumour growth, vascularisation initiation and therapeutic responses to clinically relevant MRTKIs. The identification of VEGF-A secretion as potential biomarker for Regorafenib response and the separation of therapeutic effects on tumour growth and neovascularisation suggests additional value of our model for response prediction to MRTKIs.